Effects of different fruit loads on berry maturity and quality in grape cultivar “Yinhong” - Lu Meidan; He Kun; Pei Qingsong; Jia Huijuan (浙江大学学报. 农业与生命科学版)
“Yinhong” grape (Vitis vinifera×Vitis labrusca) cultivar has many excellent characteristics, such as strong resistance, high branching rate and extensive management. The maturation of this cultivar is mainly in the middle of August, and it is one of the most promising popularized varieties after “Kyoho” and “Fujiminori” in Zhejiang Province. In recent years, with the development and promotion of protected cultivation technology, the grape picking tourism industry was booming, which undoubtedly had wider requirement for the maturity of grape. However, there exists excessive load to adjust maturity and delay picking in sightseeing orchard in production, and the effect of excessive load on adjusting maturity is not clear yet, and especially its effect on grape quality after delaying picking had not been reported. Therefore, the aim of this research is to study the effect of different load levels on berry maturity and quality.Three-year-old “Yinhong” trees were used in experiment. Three fruit load levels were designed including 2 kg/m2 (1 250 kg/667 m2), 3 kg/m2 (1 875 kg/667 m2), 4 kg/m2 (2 500 kg/667 m2) by cluster and fruit thinning. Fruit was picked when berry seed was brown and fruit mass did not increase. The quality indexes such as fruit mass, color, hardness, fruit total soluble solids (TSS), titration acid (TA) were determined at harvest.The results showed that the growing curves of different fruit loads were the same pattern, showing a double “S” curve. With the growing of the fruit, fruit diameter of 2 kg/m2 load level was highest from hardcore to maturity period, but there was no significant difference among three levels. According to the standard of harvest, both load levels of 3 and 4 kg/m2 could delay fruit ripening, and especially 4 kg/m2 could effectively delay fruit maturity by 42 days compared to 2 kg/m2. The TSS content decreased after delaying picking a week, and could not reach 17% at last for 4 kg/m2. The TA content of 2 kg/m2 load level was highest. With delaying the picking of grapes, TA content was decreased after maturity. Fruit of 4 kg/m2 load level had lower hardness compared with other two levels at maturity and was no significant change with delaying picking. The fruit masses of 3 and 4 kg/m2 load levels were lower than 2 kg/m2, but there were no significant difference among them. Color index of red grape of 4 kg/m2 load level was significantly lower than others. Anthocyanin content of 4 kg/m2 was reduced by 42% compared with 2 kg/m2. The quality indexes of 3 kg/m2 load level had large fluctuation, but the mean content was between 2 and 4 kg/m2 load levels. The data in spring of 2013 showed that the 2 kg/m2 load level had higher germination rate and was easy to produce double buds than 3 and 4 kg/m2, however, there was no significant difference between latter two levels. The load level of 4 kg/m2 reduced the flower number by 20.1% and flower length by 19.76%, compared with 2 kg/m2 load level.In conclusion, 3 and 4 kg/m2 load levels can delay fruit maturity, however the fruit quality of 4 kg/m2 load level is bad, such as soft fruit, low TSS and anthocyanin contents. After maturity, the flavor quality of 4 kg/m2 load level decrease quickly with delaying picking. Meanwhile, the flower quality is poor in the following year. The fruit mass, hardness and anthocyanin content in the 3 kg/m2 load level are also lower than 2 kg/m2. So higher fruit load had negative effect on fruit quality and vine potential, and it is not suggested to use in production unless it is necessary. Therefore, 2 kg/m2 load level of “Yinhong” grape is recommended in the production.